2011
DOI: 10.1126/science.1206727
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Mitochondrial Priming Correlates with Clinical Response to Cytotoxic Chemotherapy

Abstract: Cytotoxic chemotherapy targets elements common to all nucleated human cells, such as DNA and microtubules, yet it selectively kills tumor cells. Here we show that clinical response to these drugs correlates with, and may be partially governed by, the pre-treatment proximity of tumor cell mitochondria to the apoptotic threshold, a property called mitochondrial priming. We used BH3 profiling to measure priming in tumor cells from patients with multiple myeloma, acute myelogenous and lymphoblastic leukemia, and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
541
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 520 publications
(573 citation statements)
references
References 35 publications
30
541
1
1
Order By: Relevance
“…[39][40][41][42] In particular, the present study utilizes full-length BH3-only proteins, which differ in the strengths of their protein-protein interactions compared with isolated BH3 peptides, 49 and places those BH3-only proteins in the context of cellular signaling networks 2,45 rather than isolated mitochondria. Thus, although BH3 profiling is being explored as a strategy to predict sensitivity or resistance of particular cell lines or cancers to specific treatments, 50 measurement of BH3-only tolerance has the potential to provide insight into endogenous signaling networks within intact cells that include BCL2 family members bound to surfaces other than the MOM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[39][40][41][42] In particular, the present study utilizes full-length BH3-only proteins, which differ in the strengths of their protein-protein interactions compared with isolated BH3 peptides, 49 and places those BH3-only proteins in the context of cellular signaling networks 2,45 rather than isolated mitochondria. Thus, although BH3 profiling is being explored as a strategy to predict sensitivity or resistance of particular cell lines or cancers to specific treatments, 50 measurement of BH3-only tolerance has the potential to provide insight into endogenous signaling networks within intact cells that include BCL2 family members bound to surfaces other than the MOM.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 This assay involves treating mitochondria or permeabilized cells with isolated BH3 peptides and measuring cytochrome c release or mitochondrial depolarization. In a recent modification termed 'dynamic BH3 profiling,' cells are exposed to potential anticancer drugs versus diluent and assayed for BIM BH3 peptideinduced mitochondrial depolarization.…”
mentioning
confidence: 99%
“…Due to the above motivated similarity in apoptosis pathways between cancer cells and cardiomyocytes, any strategy that aims to protect cardiomyocytes while killing cancer cells would aim to exploit differences in apoptosis likelihood rather than invoking distinct apoptosis pathways [43][44][45]. To this end, the Deshmukh lab has shown that differentiated rat cardiomyocytes, similar to primary neurons, have down-regulated levels of the pro-apoptotic APAF-1 and increased expression of the anti-apoptotic XIAP compared to less differentiated cells.…”
Section: Are Differentiated Cardiomyocytes Less Likely To Succumb Tomentioning
confidence: 99%
“…In the context of cancer cells this mechanism was coined as apoptosis priming, aiming to explain why cancer cells are more susceptible to chemotherapy than normal cells. Specifically, proponents of the priming hypothesis such as the Letai group suggest that cancer cells increase their apoptosis likelihood in response to continuous somatic attack by the immune system [45,54], making them more likely than somatic cells to respond to cytotoxic chemotherapy. Indeed, we observe some parallelism between cancer cells primed by somatic apoptosis [45,55] and cardiomyocyte being exposed to (sub-lethal) DOX with respect to metabolic programming and apoptosis sensitization ( Figure 2).…”
Section: Does Dox Exposure Change Apoptosis Likelihood To Later Somatmentioning
confidence: 99%
See 1 more Smart Citation